2011
DOI: 10.5194/acp-11-503-2011
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of non-methane hydrocarbons in Asian summer monsoon outflow observed by the CARIBIC aircraft

Abstract: Abstract. Between April and December 2008 the CARIBIC commercial aircraft conducted monthly measurement flights between Frankfurt, Germany and Chennai, India. These flights covered the period of the Asian summer monsoon (June-September), during which enhancements in a number of atmospheric species were observed in the upper troposphere over southwestern Asia. In addition to in situ measurements of trace gases and aerosols, whole air samples were collected during the flights, and these were subsequently analyze… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
63
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 57 publications
(71 citation statements)
references
References 52 publications
(65 reference statements)
8
63
0
Order By: Relevance
“…Schuck et al (2010) showed that air masses sampled north of 30 • N generally travel for more than a week, in contrast with air masses south of 30 • N which had ground contact within the last four days prior to sampling. Baker et al (2011) confirmed that in the southern monsoon region, sampled air masses travelled 3 to 6 days before sampling, and 9 to 12 days in northern monsoon region. This is consistent with the summer BL air mass fingerprint mostly encountered over CSChi andSCSea (in 2006 and, but rarely encountered over Northern Asia.…”
Section: Two Contrasted Transport Conditions: Rapid Uplifting Of Pollsupporting
confidence: 61%
See 1 more Smart Citation
“…Schuck et al (2010) showed that air masses sampled north of 30 • N generally travel for more than a week, in contrast with air masses south of 30 • N which had ground contact within the last four days prior to sampling. Baker et al (2011) confirmed that in the southern monsoon region, sampled air masses travelled 3 to 6 days before sampling, and 9 to 12 days in northern monsoon region. This is consistent with the summer BL air mass fingerprint mostly encountered over CSChi andSCSea (in 2006 and, but rarely encountered over Northern Asia.…”
Section: Two Contrasted Transport Conditions: Rapid Uplifting Of Pollsupporting
confidence: 61%
“…The summer monsoon affects the composition of the UT by dynamical and meteorological processes, basically strong and rapid convection lifting of boundary layer air masses combined with high precipitation affecting emissions from certain sources. Consistent enhancements of CO, H 2 O, CH 4 , N 2 O and nonmethane hydrocarbons were observed with CARIBIC over South Asia in summer 2008 Baker et al, 2011). A concomitant decrease of ozone was also observed by CARIBIC .…”
Section: Two Contrasted Transport Conditions: Rapid Uplifting Of Pollsupporting
confidence: 54%
“…8c). These types of mixing lines in the troposphere could result from one or a combination of the following: (i) mixing between stratospherically and tropospherically influenced air masses, (ii) mixing between photochemically aged and freshly uplifted lower-tropospheric air and (iii) an O 3 -depleting photochemical regime (Baker et al, 2011). While the latter is unlikely in the ASMA (Fig.…”
Section: Co Versus O 3 (Fig 8a-c)mentioning
confidence: 99%
“…The strong circulation of the anticyclone acts to isolate air, and because this isolated air is tied to the outflow of deep convection, the anticyclone often has a distinct chemical signature [Dethof et al, 1999;Randel and Park, 2006;Park et al, 2007Park et al, , 2008Baker et al, 2011]. The UTLS anticyclone is a seasonal feature, beginning in June and ending in September.…”
Section: Introductionmentioning
confidence: 99%